A Comparison of Quadriceps Tendon Autograft With Bone-Patellar Tendon-Bone Autograft and Hamstring Tendon Autograft for Primary Anterior Cruciate Ligament Reconstruction: A Systematic Review and Quantitative Synthesis. Issue 4 (July 2021) - Ajrawat, Prabjit; Dwyer, Tim; Whelan, Daniel; Theodoropoulos, John; Murnaghan, Lucas; Bhargava, Manoj; Ogilvie-Harris, Darrell; Chahal, Jaskarndip
Abstract : Objective: There is growing enthusiasm for the increased use of quadriceps tendon (QT) autograft for primary anterior cruciate ligament reconstruction (ACLR). The purpose of this analysis was to synthesize and quantitatively assess the available evidence comparing QT autograft with hamstring tendon (HT) and bone-patellar tendon-bone (BPTB) autografts, regarding functional outcomes, knee stability, anterior knee pain, and revision rates. Data Sources: A search in MEDLINE, EMBASE, PubMed, and the Cochrane Central Register of Controlled Trials for eligible studies up to May 2018 was conducted. Two reviewers selected studies based on inclusion criteria and assessed methodological quality. Outcomes analyzed were anterior knee pain, graft failure rates, knee stability, functional outcomes, and adverse events. Pooled analyses were performed for continuous and dichotomous variables where appropriate. Main Results: Ten studies (1 randomized trial and 9 nonrandomized cohorts) met our inclusion criteria, which included 1398 patients. The analysis showed no statistical difference in anterior knee pain when comparing QT and HT autografts, but a significant difference between QT and BPTB autografts [odds ratio, 0.15 (95% confidence interval, 0.08-0.27); P < 0.001]. There were no differences between all 3 autografts in revision rates, knee stability, and patient-reported functional outcomes. Conclusions: Quadriceps tendon autograft is a suitable graft alternative for primary ACLR, as it achieves good clinical outcomes with a low incidence of anterior knee pain. Given the limited quality of the included studies, there is a need for a well-designed multicenter randomized control trial comparing QT autograft with other primary ACL autografts to confirm our findings. Level of Evidence: Level IV systematic review.